Racial-ethnic Identity in Context: Examining Mediation of Neighborhood Factors on Children’s Academic Adjustment - Witherspoon, Dawn P. (Am J Community Psychol, 2016)
Research consistently shows that neighborhood socio-demographic characteristics and residents’ neighborhood perceptions matter for youth well-being, including a positive sense of racial-ethnic identity. Although elementary-school children are likely in the earlier phases of identity formation, the authors examined whether objective and subjective neighborhood characteristics are related to their racial-ethnic identity and, in turn, their academic adjustment. A diverse sample (30.4% AA, 35.2% White, 12.3% Latino, & 22.0% Other) of 227 children in Grades 2 through 5 were surveyed in afterschool programs. Bivariate correlations showed that youth living in disadvantaged neighborhoods reported more barriers due to their race-ethnicity, but these barriers were not related to their sense of academic efficacy. Residing in a disadvantaged neighborhood was unrelated to youth’s academic self-efficacy. However, path analyses showed that positive neighborhood perceptions were associated with a stronger sense of race-ethnicity (i.e., affirmation and belonging), which was in turn related to greater academic efficacy. These results suggest that neighborhood connection provides a source of affirmation and value for young children, helping them to understand who they are as part of a racial-ethnic group and helping to foster a sense of future achievement opportunities. This study provides additional evidence that along with other important proximal contexts (e.g., family, school), young children’s neighborhood context is important for development. Results are discussed to highlight environmental influences on young children’s awareness of race-ethnicity and the implications of the combined impact of neighborhood and racial-ethnic identity on psychosocial adjustment.